Assimilating in Alternative Spaces of Possibility: A Study of Suniti Namjoshi’s Select Works - Tanima Shome (The Creative Launcher, 2017)
Postcolonial queer literature calls into question and dismantles the very notion of a community’s assumption of heterosexism as the norm and ‘queer’ ones as deviant. Postcolonial narratives do not endorse the way in which power has structured spaces; it rather debunks and interrogates the heteronormative configuration of space. These narratives present a departure from the Eurocentric queer accounts which make them essentially postcolonial. It critiques the notion of ‘compulsory heterosexuality’ which in the words of Vijayasree “is a repressive social structure that systematically subordinates women.” This paper attempts at exploring the different facets of lesbian desire and identity in Namjoshi’s narratives. It further interrogates the heteropatriarchal space of the family, home and on the whole, the diasporic community .It also endeavors to focus on the politics of exclusion depicted in Namjoshi’s select works that lead to momentary disillusionment, yet forging a space of possibility and recognition which emerges as a site of contestation from the captivity of heterosexist body and opposing Orientalism.